6g-4(-6+3g)=1-g

Simple and best practice solution for 6g-4(-6+3g)=1-g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6g-4(-6+3g)=1-g equation:


Simplifying
6g + -4(-6 + 3g) = 1 + -1g
6g + (-6 * -4 + 3g * -4) = 1 + -1g
6g + (24 + -12g) = 1 + -1g

Reorder the terms:
24 + 6g + -12g = 1 + -1g

Combine like terms: 6g + -12g = -6g
24 + -6g = 1 + -1g

Solving
24 + -6g = 1 + -1g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add 'g' to each side of the equation.
24 + -6g + g = 1 + -1g + g

Combine like terms: -6g + g = -5g
24 + -5g = 1 + -1g + g

Combine like terms: -1g + g = 0
24 + -5g = 1 + 0
24 + -5g = 1

Add '-24' to each side of the equation.
24 + -24 + -5g = 1 + -24

Combine like terms: 24 + -24 = 0
0 + -5g = 1 + -24
-5g = 1 + -24

Combine like terms: 1 + -24 = -23
-5g = -23

Divide each side by '-5'.
g = 4.6

Simplifying
g = 4.6

See similar equations:

| -5p+6+6p=11 | | -3/5-3/10 | | 8.4x+16.28=-11.6+16.04 | | 3-/5-3/10 | | x^2+8x+8=3x+4 | | 24+16x=75+17x | | (2z-3)(z+4)=(3z-2)(z+6) | | (-5p+8)=(7p-5) | | 4x+2=3(x-3)+5 | | 0=-5t+15 | | 7.6x-1.1=29.3 | | 2[3-(-8x-8)]=80x+86 | | 1.7+x=7.1 | | 2+1x=1 | | 2l+2(70)=600 | | 4/5x-8=9/5x | | -2y-16=0 | | x^2-9x-14=-6x+4 | | 3/4*.1=8 | | 3(6z-1)-4(z+2)=6(z+1) | | x^2-2x-27=8 | | 2(56-13)= | | -1=b^4-7 | | Abs(x-2)=22 | | 1.92-0.33= | | 3-2/2--4 | | -8u=24 | | -15-2x=16-1(3x-9) | | X(2x-2)+x(6x-3)=(8x+9)(x-2) | | 5x+10+4(X+2)=3(X+8)+12 | | 2y^2=-200 | | 9/2*w=-7 |

Equations solver categories